2018
DOI: 10.1007/s00402-018-2947-4
|View full text |Cite
|
Sign up to set email alerts
|

Muscle–tendon-related abnormalities detected by ultrasonography are common in symptomatic hip dysplasia

Abstract: Muscle-tendon-related abnormalities detected by ultrasonography in the hip and groin region are common in patients with symptomatic hip dysplasia, and the ultrasonography findings of the iliopsoas and gluteus medius/minimus tendons are weakly to moderately correlated to pain related to muscles and tendons in these structures. Both the iliopsoas and the gluteus medius/minimus have a pronounced stabilizing role in the dysplastic hip joint, and the common muscle-tendon-related abnormalities in these patients may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The muscles around the hip joint (musculus iliopsoas, gluteus medius, and minimus) are thought to be crucial in stabilizing the hip joint in patients with DDH due to shallow and steep acetabular roof [6]. Gluteus medius is the hip adductor group muscle that plays an essential role in balancing the abduction force around the hip joint like other abductor muscles of the hip (musculus piriformis, tensor fascia lata, gluteus maximus, and minimus) [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The muscles around the hip joint (musculus iliopsoas, gluteus medius, and minimus) are thought to be crucial in stabilizing the hip joint in patients with DDH due to shallow and steep acetabular roof [6]. Gluteus medius is the hip adductor group muscle that plays an essential role in balancing the abduction force around the hip joint like other abductor muscles of the hip (musculus piriformis, tensor fascia lata, gluteus maximus, and minimus) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Domb et al reported that 18% of patients with symptomatic hip dysplasia had muscle-tendon-related abnormalities in the iliopsoas tendon determined in hip arthroscopy [29]. Jacobsen et al [6] evaluated patients with unilateral and bilateral hip dysplasia with musculoskeletal ultrasonography and concluded that pain in these patients was concerned with both iliopsoas and the gluteus medius and minimus. In that study, tendon-related abnormalities were identified in iliopsoas tendon in 50%, in adductor longus tendon in 31% and gluteus medius/minimus tendons in 27% of the patients [6].…”
Section: Clinical Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Further details on study design was reported in our previous studies on the same study population, reporting ultrasonography-detected abnormalities and prevalence of muscle–tendon pain prior to PAO (Jacobsen et al. 2018a, b).…”
Section: Methodsmentioning
confidence: 99%